Graphic anaesthesia : diagrams, tables and equations for trainee anaesthetists /: diagrams, tables and equations for trainee anaesthetists. (2015) - Hooper, Tim; Hooper, Tim; Nickells, James; Walton, Benjamin; Payne, Sonja; Pearson, Annabel
No abstract available